Lactation Characteristic of Etawah Crossed Breed Goats Under Intensive Management - Yuni Suranindyah; Budi Prasetyo Widyobroto; Sulvia Dwi Astuti; Tridjoko Wisnu Murti; Adiarto Adiarto (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The study aimed to describe lactation characteristic of Etawah Crossed Breed goats raised under intensive management. The study located in BBPTU HPT Baturraden, Purwokerto, used 27 female pregnant goats, at 24 to 27 months old. The goats were managed followed standard operating procedure of the research institute. The data consisted of body size and body weight, colostrum and milk yield, lactation period and reproductive performance. The results showed the average of daily milk yield, lactation period, total milk and colostrum production in first lactation were 960±340 mL/day, 157±41 days, 114,720±68,900 mL and 415±240 mL/day. The proportion of monthly milk production from initial lactation to dry off were 21.27, 22.17, 20.18, 17.29, 12.52, 9.13, and 5.65% of total lactation yield, respectively. Peak production ranged from first to second months of lactation, the highest was in the week 4th, averaged of 1080 mL/day. Production persistency was 66.39%. The rate of increase toward peak was 5.60%/week and rate of decline from peak was -3.92% of milk yield in the previous week. Trend equation of lactation curve was Y = 8412.7 –233.65 x. Means period of postpartum mating, service per conception and body condition score were 88.7±39.2 days, 1.2 and 3.45, respectively. There was no correlation between postpartum mating, body condition score and milk production. The study concluded that Etawah Crossed Breed goat under intensive management had short lactation period, early peak production, low persistency. The dry period was estimated 3 months and pregnancy occurred after peak production.